Dynamic modeling and controllability analysis of DME production in an isothermal fixed bed reactor (Chemical Engineering Research Bulletin, 2015)
In this study, to enhance Dimethyl Ether (DME) production from methanol dehydration, an isothermal fixed-bed reactor has been modeled heterogeneously against a commercial adiabatic reactor at dynamic condition. A sensitivity analysis has been carried out to evaluate the influence of input variables on the process conditions using considered dynamic model. The results of sensitivity analysis showed that the feed composition is the main input variable in this system. Also, the process controllability has been investigated using a conventional feedback PID controller. The outlet DME composition from the reactor and circulated boiling water pressure in the steam drum are selected as controlled and manipulated variables, respectively. The responses of the control system to disturbance rejection and setpoint tracking showed that the considered control structure can maintain the process at the desired condition. DOI: http://dx.doi.org/10.3329/cerb.v17i1.22917 Chemical Engineering Research Bulletin 17(2015) 40-51